Penerapan Model Pembelajaran Project Based Learning (PjBL) Melalui Pembelajaran Daring Terhadap Hasil Belajar Termokimia Di Sma Kristen Dumoga - Ravelita Lastriawati Bullu; Jeanne Tuerah; Soenandar Tengker (Chemistry Department, Universitas Negeri Manado, 2022)
The purpose of the study was to determine the effect of the application of the Project Based Learning (PjBL) Learning Model on Thermochemical Materials Through Online Learning at Dumoga Christian High School. This research was conducted in class XI Science at SMA Kristen Dumoga in the academic year 2021/2022. A total of 20 students of class XI IPA 1 were assigned as research samples. Based on the test data of the t-test hypothesis, the tcount value is 24,090 with a ttable value of 2,024. And the significant level used is = 0.05 with degrees of freedom n1 + n2 -2 (20+20-2) = 38. By looking at the values of tcount and ttable, we get tcount > ttable, meaning Ho is rejected and Ha is accepted. Based on the increase test (N-gain) obtained 0.77 with high criteria. Thus, it can be concluded that the application of the online learning project based learning model on thermochemistry learning outcomes in Dumoga Christian High School.